The Conception of Ibrahim Amin Al-shawrabi and Ali Abbas Zalikhe from 32th Sonnet of Hafez Shirazi's Sonnets (Comparative Study) - Mirghaderi, Seyyed Fazlollah; Havaej, Fatemeh (LANGUAGE ART, 2020)
The importance of comparative research lies in revealing the leading technical foundations of modern literary criticism, Literature in different eras does not involve itself, but rather relates to other global literatures. The theory of receptivity appeared in the last decades of the nineteenth century to confirm the presence of the reader, in exchange for a number of statements. The recipient's culture holds great importance in this work, because it is the main tributary in every mental work, because the author needs cultural and imaginative richness to write the literary text. For example; among the recipients who has translated the poems of Hafez Al-Shirazi were the Egyptian writer Ibrahim Amin Al-Shawarbi and the Syrian writer Ali Abbas Zulekhe. We have tried to study the 32th sonnet of Hafez 's sonnets and the study of receiving recipients, and to compare their receiving responses. One of the results we have obtained is that recipients had not delve into special meanings, terms, and special titles. Finally, it became clear to us that receiving Al-Shawarbi was more important than receiving Zulekhe; because Al-Shawarbi was aware of the Iranian culture and relationship. However; the conception of Zulekhe in terms of sensations and emotion, it is better to have a smoother experience than Al-Shawrabi.